The Influence Of Audit Probability, Sanction Severity, And Social Norms On Enforced Tax Compliance With Patriotism As Moderation - Marfiana, Andri; Santoso, Rizky Aji (WIM Solusi Prima, 2024)
This study aims to determine the effect of audit probability, sanction severity, social norms on enforced tax compliance with patriotism as a moderator variable. The object of this research is an individual who carries out independent work in Jakarta and its surrounding areaThis study uses primary data consisting of 200 respondents' answers that have been collected. This subject have choosed because their income is not always deducted from tax by withholding system, making it prone to tax fraud. Data analysis was performed using the Partial Least Square (PLS) model with the Structural Equation Modeling (SEM) method. The test results show that audit probability, sanction severity, social norms, patriotism partially have a significant positive effect on enforced tax compliance, while patriotism manages to moderate the effect of social norms on enforced tax compliance with a negative relationship. This indicates that a sense of patriotism is not the main element that moderates tax compliance. Although patriotism directly affects tax compliance. The Government should have law enforcement policy to taxpayers dan build social norms which encourage taxpayers to obey their tax obligation.